Politik Hukum Dan Sistem Pendidikan Nasional: Pengaruh Politik Hukum Terhadap Sistem Pendidikan NAsional - , Susanto; , wardah Yuspin, S.H, M.Kn., Ph.D; , Dr. Nurhadiantomo (2016)
ABSTRACT This thesis is the result of research literature entitled "Politics of Law and the National Education System: Political Influence Law Against National Education System. This research is to answer the question of How Political relations law at the National Education System In Indonesia, How to Influence Political Influence Law Against National Education System. To answer the above questions, collection of data in research reserch libary is a documentary techniques, which are collected from archives tela`ah or existing literature on secondary law. The study concluded that the political forces have influenced the formation of a legal product, one product law on the national education system. In working out and organize a national education system the Indonesian government has a rule set forth in Article 31 paragraph (3) and (4) of the Constitution of 1945. The provision in the Constitution are then followed up in the form of Act No. 20 of 2003 on the System National Education which is the result of a political consensus. There are at least five political influence to education, namely: (a) Political influence on educational activities in the creation of values and expectations of citizens as to what is required by the state, (b) the political influence on the education budget, (c) the political influence on education resources such as teacher salaries, supporting infrastructure of learning activities, and teacher training, (d) the political influence on the school system as school structure, reward systems for teachers and admissions system, (e) the political influence on the quality of graduates that diihat of how political education graduates behave, behave cultural, economic behavior and social behavior. From the above results, the Indonesian government should be able to create a legal product national education system which will improve the quality, relevance and competitiveness of education outcomes in Boyolali in particular, and the national education system in general. Keywords: Politics, Law, systems, Education